High Resolution Seismic Refraction Tomography for Determining Depth of Blast Induced Damage in a Mine Wall - Janae Singer; Stephan Iversan (International Society of Explosives Engineers, 2009)
High resolution seismic refraction tomography has proved to be a useful tool to effectively estimate depth of blast induced damage in rock. Excavation blast damage can be as shallow as 1 to 2m (3 to 7ft) and requires resolution at a fraction of a meter for effective imaging. We used an accelerometer with flat frequency response to 1000Hz to record data at spacings of approximately 0.25 to 0.5m (0.8 to 1.6ft) along mine walls. The resulting tomograms of P-wave velocity show low velocity zones which we interpret as residual fracturing from blasting. Experiments on a concrete test block and at two underground mine locations give results that are consistent with fractured rock transitioning to competent rock.